DEVELOPING GENIAL.LY BASED SELF-ACCESS LANGUAGE LEARNING SUPPLEMENTARY MATERIALS TO FACILITATE STUDENTS' LEARNING AUTONOMY IN TERTIARY EDUCATION - Fitriani, Ika (Premise: Journal of English Education and Applied Linguistics, 2025)
Building learning autonomy is a pivotal aspect in higher education. Students should be able to be more independent, rather than relying heavily on teacher-directed activities within the classroom. It is crucial to provide self-access materials that align with students' learning needs. This current research, therefore, aimed at developing interactive English supplementary materials using Genial.ly for promoting students' autonomous learning. Genial.ly has been proven to be a promising application; however, the use of Genial.ly to develop English for Specific Purposes (ESP) self-access learning materials for EFL Nursing students is still understudied. Following the research and development stages, which included planning, development, and evaluation, the findings showed that the average scores for language and media expert validation were 4.8 and 4.7, respectively. Following this, the researcher conducted the first revision and a small-scale trial, yielding an average score of 4.1. Based on the results, it can be concluded that the learning product meets the standard and is feasible to be implemented as supplementary materials to help both teachers and students within the English teaching and learning process. Further classroom action research (CAR) or experimental design is highly recommended to investigate the effectiveness of the Genial. Ly-based learning product. The implementation of Genial. Ly-based interactive English supplementary materials also required further and larger feedback from the broader user base to inform future product development that meets the students' needs.